Penerapan Stretching untuk Peningkatan Sensitivitas Kaki dan Ankle Brachial Index (ABI) pada Lansia dengan Diabetes Mellitus Tipe II yang Mengalami Parestesia : THE APPLICATION OF STRETCHING TOWARDS THE NURSING PROBLEM OF PERIPHERAL PERFUSION IS NOT EFFECTIVE FOR INCREASING FOOT SENSITIVITY AND ANKLE BRACHIAL INDEX (ABI) IN ELDERLY PEOPLE WITH TYPE II DIABETES MELLITUS EXPERIENCING PARESTHESIA - Clamiza, Zahara (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: to identify provides an overview of the results of theNursing Profession Practice with the Application of StretchingApplication to the Problem of Peripheral Perfusion Nursing isIneffective for Increasing Foot Sensitivity and Ankle BrachialIndex (ABI) in the Elderly with Type II Diabetes Mellitus inSungai Putih Village, Tapung District, Kampar Regency.Methods: This article which is used in the implementation ofnursing interventions providing Stretching Against IneffectivePeripheral Perfusion Nursing Problems in the elderly withType II Diabetes Mellitus. The implementation was carried outfor 7 consecutive days starting from April 17-23, 2025. Thesubjects in this application were 2 elderly people.Results: The results of this case study are the lowest total valueof right and left foot sensitivity of 4 and the highest total valueof right and left foot sensitivity of the elderly is 9, there is asignificant increase in the sensitivity of the right and left footareas in the elderly with Type II Diabetes Mellitus. As well asan increase in the measurement value of the Ankle BrachialIndex (ABI) in the Elderly with Type II Diabetes Mellitus, withthe highest measurement value of the Ankle Brachial Index(ABI) of 150/100 mmhg and the lowest measurement value ofthe Ankle Brachial Index (ABI) of 120/60 mmhg, there is asignificant increase in the Ankle Brachial Index (ABI) in theElderly with Type II Diabetes Mellitus.Conclusion: The advantage of applying stretching to patientswith diabetes mellitus is to increase sensitivity and anklebrachial index and prevent complications associated withperipheral nerve damage.